A Novel Non-Linear Strip-Line Kicker Driven by Fast Pulser in Common Mode. (November 2019) - Chen, J.; Wang, L.; Li, Y.; Shi, H.; Duan, Z.; Wang, N.; Huo, L.; Wang, G.
Abstract: The next generation storage ring-based light sources adopt multi-bend achromat lattices to achieve a low emittance. The dynamic apertures of these machines are usually less than 10 mm so that the traditional pulsed local bump injection is difficult to achieve. Off-axis injection with a pulsed multipole or a non-linear kicker could be a viable solution which requires a moderate dynamic aperture of a few mm. In this paper, a novel non-linear kicker design is presented. Unlike pulsed sextupole or nonlinear kicker magnet, the nonlinear kicker we proposed is a traveling wave kicker with 2 strip-line electrodes driven by a nanosecond-level fast pulser in common mode. The disturbance to the stored beam is minimal since the perturbation is limited to the target bunch alone.